Contemporary Art vs Totalitarian Art: Semiotic Analysis - Ukhov, Artem; Simonyan, Eleonora; Muradyan, Susanna (Տիգրան Մեծ)
The article provides a semiotic analysis of the types of totalitarian culture and its manifestation in art, both classical and modern. On the basis of totalitarian culture semiotic analyses, it is shown that mass culture (and its attributes) may be considered a modern type of totalitarian culture. Particularly, the antidogmatic and antitotalitarian essence of the contemporary art phenomenon is highlighted. Based on the semiotic methodology, a key moment of demarcation between contemporary art and the „totalitarian‟ one has been emphasized. The conclusion about the inconsistency of signs and symbols of contemporary as compared to totalitarian art has been drawn. Contemporary art could be referred to as a tool for tracing, revealing and even combating totalitarianism in culture and life.
Keywords: Philosophy of Art